A ferritin-targeted biohybrid triggering ferroptosis immunotherapy via activating endogenous iron and replenishing exogenous iron simultaneously - Shupei Sheng; Yan Zhang; Limin Jin; Weiting Sun; Dunwan Zhu; Lin Mei; Xia Dong; Feng Lv (Nature Communications)
Abstract The key to achieving synergistic ferroptosis immunotherapy is enhancing the iron content in tumor cells, improving specific immunity, and regulating the tumor microenvironment. In this study, a drug-free biohybrid system targeting ferritin is developed using M1 macrophage microvesicles and HKN15-modified Prussian blue nanoparticles for synergistic ferroptosis immunotherapy. HKN15-modified nanoparticles simultaneously enhance iron content by activating endogenous iron ions and replenishing exogenous iron ions, which disrupts iron homeostasis for inducing ferroptosis in tumor cells. Photothermally enhanced ferroptosis based on Prussian blue nanoparticles also stimulates dendritic cell maturation. Moreover, M1 vesicles and iron ions from Prussian blue nanoparticles promote macrophage polarization to improve specific immunity. The mutual promotion of ferroptosis and antitumor immunity effectively results in a synergistic therapeutic circuit for inhibiting tumor growth and preventing cancer recurrence and metastasis in 4T1 tumor-bearing female mice, thus offering a promising strategy for drug-free biohybrid system-mediated ferroptosis immunotherapy.